Performance Appraisal of Managerial Civil Servants Using the ANP Method and Rating Scale at the Human Resource Development Agency - N, Atikah; Sari, R.F.; Lubis, R.S. (Journal of Research in Mathematics Trends and Technology, 2021)
Employee performance appraisal is very necessary to know the skills or abilities of each employee. Employee performance appraisal carried out at the Human Resources Development Agency still require employee performance evaluations for the performance of each employee. The purpose of this study was to determine the performance of employee using the Analytic Network Process and Rating Scale methods, where the ANP was used to weight each criteria and sub-criteria with the result of the weighting of the criteria namely: service orientation (0,051197), Integrity (0,254363), commitment (0,150948), discipline (0,190137), cooperation (0,353354) and for the weight of each sub-criterion, being friendly (0,060724), completing work quickly and precisely (0,129413), working properly, honestly and regularly (0,080407), working well even though not supervised by the leadership (0,132196), have goog character (0,041760), have loyalty (0,175543), have responsibility (0,108780), do not delay work (0,069031), never go absent without clear reasons (0,107260), are able to work togather with colleagues (0,043688), like to help colleagues who are in trouble (0,014759), able to communicate well (0,036438). While using the Rating Scale methods has different values, employees with the highnest performance is Rosniari (4,762981) and lowest is Masdalifah (3,770376)